Multi-Criteria Decision Analysis for Fire Patrol Helicopters Selection Using AHP-Entropy-TOPSIS - Suprapto, Ready Kresna Nanda; Setiawan, Andri Dwi (Langit Biru: Jurnal Ilmiah Aviasi, 2025)
Forest fires pose a significant threat both locally and globally, with indirect impacts including global air pollution and human health issues. Aerial patrols using helicopters are a crucial measure in wildfire management. However, selecting the appropriate helicopter model involves multiple factors. Poor decision-making can lead to increased operational costs, accidents, and mission failure. To address this, operators must choose the most suitable helicopter for fire patrol operations. This study aims to enhance the decision-making process by integrating subjective and objective weighting methods in Multi-Criteria Decision Making (MCDM). Subjective weights are determined using the Analytic Hierarchy Process (AHP), while objective weights are derived from the Entropy method. The Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) is applied to identify the optimal helicopter model. By analyzing the combined weighting results, this study provides a robust decision-support tool, ensuring the selection of the most efficient and effective helicopter for wildfire patrols.